Improving Children's Gross Motor Skills Through Traditional Games in Group B of Ululjadi Kalora Kindergarten - Mardiana Mardiana; Andi Agusniatih; Ika Juhriati (Universitas Al-Hikmah Indonesia, 2025)
Gross motor development is an important aspect in early childhood growth because it plays a role in training balance, coordination, agility, and muscle strength that supports daily activities, so that targeted stimulation through fun play activities is needed. One relevant game is hopscotch, which requires children to jump, maintain balance, and coordinate body movements so that it can stimulate gross motor skills optimally. This study uses the Classroom Action Research (CAR) design model of Kemmis and McTaggart with the stages of planning, implementation, observation, and reflection, and combines qualitative analysis through reduction, presentation, and drawing conclusions, and quantitative analysis by calculating the percentage of children's development in the categories of Not Yet Developing (BB), Starting to Develop (MB), Developing According to Expectations (BSH), and Developing Very Well (BSB). The results of the study showed a significant increase in children's gross motor skills from pre-cycle to cycle II in the aspects of balance, coordination, agility, and muscle strength, so it can be concluded that hopscotch games are effective as an active, fun, and contextual learning strategy in supporting the optimal development of early childhood gross motor skills.